2012
DOI: 10.1109/led.2011.2175357
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Poly-Si Thin-Film Transistors With L-Fin Channels

Abstract: For the first time, we construct poly-Si thin-film transistors (TFTs) with novel L-shaped poly-Si fin channels (poly-Si TFTs with L-fin channels, called LFin-TFTs). The L-fin channels of LFin-TFTs are similar to the multiple-gated fin channels of FinFETs. The LFin-TFTs exhibit a low supply gate voltage (3 V), a good subthreshold swing (SS) ∼190 mV/dec, and a high on/off current ratio (I ON /I OFF ) > 10 6 (V D = 1 V) without hydrogenrelated plasma treatments. After Ni salicidation, the devices exhibit steep SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…unfortunately, Ultra-thin active layer (below 10 nm) leads to severe mobility degradation which can be caused by the increased surface roughness scattering. Some researchers have indicated that planar short-channel poly-Si TFTs show undesirable short-channel effects (SCEs), including threshold-voltage (Vth) roll off, poor subthreshold swing (SS), and large drain-induced barrier lowering (DIBL) owing to the poor gate electrostatic control [5] [6]. Thus great efforts on nonplanar device structures have been made for better gate electrostatic control of the channel potential, for example double gated, triple gated, Π gated, Ω gated, etc.…”
Section: Introductionmentioning
confidence: 99%
“…unfortunately, Ultra-thin active layer (below 10 nm) leads to severe mobility degradation which can be caused by the increased surface roughness scattering. Some researchers have indicated that planar short-channel poly-Si TFTs show undesirable short-channel effects (SCEs), including threshold-voltage (Vth) roll off, poor subthreshold swing (SS), and large drain-induced barrier lowering (DIBL) owing to the poor gate electrostatic control [5] [6]. Thus great efforts on nonplanar device structures have been made for better gate electrostatic control of the channel potential, for example double gated, triple gated, Π gated, Ω gated, etc.…”
Section: Introductionmentioning
confidence: 99%